Combination of Aspartate Aminotranferase and Tumor Necrosis Factor-alfa as Non Invasive Diagnostic Tools for Non Alcoholic Steatohepatitis (NASH) - Hery D Purnomo; Farmaditya EF Mundhofir; Kasno Kasno; Eddy Sudijanto; Darmono Darmono; Daldiyono Hardjodisatro; R Djokomoeljanto1; Sultana MH Faradz (Acta Medica Indonesiana)
Aim: to develop a non-invasive diagnostic test for non-alcoholic steatohepatitis NASH. Methods: this is a cross-sectional study on non-alcoholic fatty liver disease (NAFLD) subjects. Sample was taken by consecutive sampling method. Diagnostic criteria of NAFLD were confirmed by liver biopsy. Clinical variables include metabolic syndrome, aspartate aminotransferase (AST), alanine aminotransferase (ALT), adiponectine, TNF-alfa, insulin, homeostatic model assessment insulin resistance (HOMA-IR) index and liver biopsy. Patients were divided into two groups based on their liver biopsy, group 1: Non-NASH (NAFLD activity score <3) and group 2: NASH (NAFLD activity score of >4). Statistical analyses were performed using Student’s t-test, Mann Whitney U, chi-square, the ROC curve, sensitivity and specificity test. Results: fifty NAFLD patients were recruited, 30 males and 20 females. Among these patients, 12 (24%) had type 2 diabetes, 36 (72%) had metabolic syndrome, the remaining 2 (4%) did not fulfilled metabolic syndrome. Liver biopsy confirmed 21 (42%) non- NASH and 29 (58%) NASH respectively. Level of AST and ALT, plasma level of adiponectine and TNF-alfa were statistically different between two groups. The AST level (>25 U/L) in combination with TNF-a (>3.28 pg/cc) demonstrated a good diagnostic accuracy for NASH (Accuracy 82%, Sensitivity 76%, Specificity 90%, PPV 92%, and NPV 73%). Conclusion: the combined diagnostic tests of AST and TNF-alfa plasma levels demonstrated a good accuracy for the detection of NASH among NAFLD patients. This combination test can be used as a noninvasive method to diagnose NASH. Key words: AST, TNF-a, diagnostic test, NASH.